Heat Transfer In Staggered Oblique Fin Microchannels - Sahar, Nurhamizah (Universiti Sains Malaysia, 2018)
Enhancement of the heat transfer performance in microchannel heat sink to handle the increased dissipation of heat from electronic components is continuously improved. Similar with oblique fin, staggered oblique fin also provides a secondary flow which improved the fluid mixing which enhance heat transfer. However, staggered oblique fin has much more breakage due to the staggered designs that improved the regeneration of the flow causing it to always be in developing state. This re-initialization of the flow effecting the thickness of the thermal boundary layer to be reduced and increasing the pressure drop thus resulting a better heat transfer performance. Therefore, two models of staggered oblique fins which differs in the height of staggered positions are modelled in order to modulate the flow in microchannel heat sinks. The Navier-Stokes momentum equation, continuity equation an energy equation are solved simultaneously by ANSYS FLUENT 18.1. Heat flux of 65 W/cm2 and inlet velocity is fixed. The pressure drop and temperature difference of the outlet and inlet of the flow in both of the staggered oblique fins are higher compared to the oblique fins. The proposed modification is found to be one of the effective ways to enhance the heat transfer performance in microchannel heat sink.